The Study of Literacy Pragmatics Approach to Moral Value in The Novel Surat Kecil Untuk Tuhan by Agnes Davonar - Kumala Sari, Tetri; Andra, Vebby; Aulia Sari, Wenny (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
This study aims to describe the form of moral values in the novel Surat Kecil untuk Tuhan and the benefits of moral values for readers in the novel Surat Kecil untuk Tuhan by Agnes Davonar. The approach used in this research is literary pragmatics approach. This research is a qualitative descriptive research. The data source in this research is the text in the novel entitled "Surat Kecil untuk Tuhan" by Agnes Davonar which contains moral values. The data collection technique is done by means of documentation and literature study. This research focuses on issues related to the analysis of moral values with a pragmatic approach. The results showed that the form of moral values has three types, namely the first form of moral values in human relations with God has variants in the form of faith and prayer to God, the second form of moral values in human relations with oneself has variants of patience, sincerity and student responsibility for education, while the form of moral values in human relations with other humans has parents' advice to children, advice between friends, parents' affection for children, children's affection for parents, affection between friends, and parents' responsibility to children. The benefits of moral values contained in the novel Surat Kecil untuk Tuhan are several variants, namely accepting God's destiny, being firm, surrendering, working hard, praying to God, not giving up easily, and not being steadfast in facing trials.